Cover Feature: SnBrP‐A SnIP‐type representative in the Sn−Br−P system (Z. Anorg. Allg. Chem. 10/2022). Issue 10 (25th May 2022) - Reiter, Felix; Pielmeier, Markus; Vogel, Anna; Jandl, Christian; Plodinec, Milivoj; Rohner, Christian; Lunkenbein, Thomas; Nisi, Katharina; Holleitner, Alexander; Nilges, Tom
Abstract : The cover picture show double‐helical SnBrP crystals grown in a vapor transport process and an illustration of the double helical structure with an outer [SnBr] and an inner [P]‐helix. The inset above the structure denotes the results of an HR‐TEM experiment where the rotating lattice character of SnBrP becomes obvious. As a result of very weak van der Waals interactions between SnBrP double helix strands, the material does not show a three‐dimensional periodic structure, and the lattice rotates slightly on a 10 nm scale (DOI: 10.1002/zaac.202100347 ).